(untitled) (Bangladesh Journal of Nuclear Medicine, 2019)
Introduction: Radioactive iodine therapy (RAIT) in patients with hyperthyroidism (HT) causes apoptosis of thyrocytes to bring about restoration of thyroid function. The aim of the study was to find the short term extent of reduction of thyroid gland volume (TGV) by non-invasive quantitative assessment using ultrasound imaging (USG). Patients and Methods: This prospective study was conducted on a group of patients who had received RAIT due to primary hyperthyroidism at National Institute of Nuclear Medicine & Allied Sciences (NINMAS). Pre-therapy work up included hormone assay and baseline measurement of TGV by US before administration of appropriate fixed dose RAIT. Short term follow-up with hormone assay and serial measurements of TGV on two occasions were done at three and six months following the RAIT. Observed temporal changes of parameters were analyzed using appropriate statistics. Results: Total 117 patients with primary hyperthyroidism had received RAIT with diagnosis of diffuse toxic goiter in 86 patients, toxic multinodular goiter in 21 cases and single toxic nodular goiter in 10 cases. There was a decline of mean TGV from the baseline level of 24 ml to 14 ml at three months followed by a further decline to 9.1 ml at six months. Thus the volume reduction of thyroid gland was calculated to be 42% at three months and 62% at six months. The volume reduction was observed to be in a correlative trend with the normalization of hormone levels. The proportion of patients who showed persistent hyperthyroidism till the study end point was 23%. Conclusion: Single dose of radioactive iodine therapy resulted in reduction of TGV up to 62% till six months after RAIT while 23% patients showed persistent hyperthyroidism. The correlative trend of volume reduction with normalization of hormone levels indicates potentiality of TGV to emerge as an adjunct to conventional assessment of treatment efficacy following RAIT. Bangladesh J. Nuclear Med. 21(2): 87-91, July 2018